Innovation an Ethics: Islamic Financial Institutions in the Modern Era - Ergiansyahda, Naura Fitri (ICO EDUSHA, 2024)
Innovation and ethics are fundamental aspects in the development of Islamic financial institutions in the modern era. Amidst technological advancements and increasingly dynamic market demands, Islamic financial institutions need to adapt to innovations such as the use of fintech, digital services, and technology-based financial products that comply with Sharia principles. These innovations aim not only to enhance efficiency and accessibility but also to attract the interest of the younger generation, who are more tech-savvy. However, the main challenge faced is ensuring that every innovation introduced remains aligned with the ethical principles of Sharia, such as justice, transparency, and social responsibility. The application of ethics in innovation is key to maintaining public trust and the legitimacy of Islamic financial institutions. This study explores the integration of innovation and ethics in the development of Islamic financial products and services, as well as their impact on the performance and reputation of these institutions. Through a qualitative approach and case analysis, this research aims to provide insights into strategies that Islamic financial institutions can adopt to achieve a balance between innovation and ethical compliance. The research findings are expected to serve as a guideline for the sustainable and relevant development of Islamic financial institutions in the digital era, while also upholding the integrity of Sharia principles. Keywords: Innovation, Ethics, Islamic Financial Institutions, Technology, Sharia Principles, Digitalization, Modern Era